BODILY PROCESSING: WHAT PROGRESS HAS BEEN MADE IN UNDERSTANDING THE EMBODIMENT OF COMPUTING SYSTEMS? - PROPERZI, Martina (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
In this article I will address the issue of the embodiment of computing systems from the point of view distinctive of the so-called Unconventional Computation, focusing on the paradigm known as Morphological Computation. As a first step, I will contextualize Morphological Computation within the disciplinary field of Embodied Artificial Intelligence: broadly conceived, Embodied Artificial Intelligence may be characterized as embracing both conventional and unconventional approaches to the artificial emulation of natural intelligence. Morphological Computation stands out from other paradigms of unconventional Embodied Artificial Intelligence in that it discloses a new, closer kind of connection between embodiment and computation. I will further my investigation by briefly reviewing the state-of-the-art in Morphological Computation: attention will be given to a very recent trend, whose core concept is that of “organic reconfigurability”. In this direction, as a final step, two advanced cases of study of organic or living morphological computers will be presented and discussed. The prospect is to shed some light on our title question: what progress has been made in understanding the embodiment of computing systems?